Shen Of The Sea Chinese Stories For Children - Chrisman, Arthur Bowie; Hasselriis, Else (New York Dutton Children's Books, 1953)
Sixteen original stories reflecting the spirit of Chinese life and thought
American Corner
Winner Of The 1926 Newbery Medal
11
Keywords: Chinese Stories; Short Stories